FRI0143 Comparison of organ damage in systemic lupus erythematosus patients with and without antiphospholipid syndrome. (1st June 2001) - Inanç, M; Öncü, S; Gül, A; Kamali, S; Çefle, A; Sayarlioglu, M; Öcal, L; Aral, O; Koniçe, M
Abstract : Background: Organ damage in systemic lupus erythematosus (SLE) may result from SLE itself or other comorbid conditions. Several items (subitems) of the SLICC/ACR damage index were previously reported as clinical manifestations associated with antiphospholipid syndrome (APS) or antiphospholipid antibodies. The contribution of APS to organ damage in SLE remains to be determined. Objectives: To determine and compare end organ damage in patients with SLE with and without APS. Methods: A preliminary analysis was performed by using the data of an ongoing study on organ damage in patients with SLE. Permanent organ damage was determined by using SLICC/ACR damage index in 106 consecutively assessed patients that were stratified according to the presence of APS. All patients fulfilled the ACR criteria for the classification of SLE. Student's t, Fisher's exact and Mann Whitney U tests were used for comparisons. Results: Twenty-one patients (19.8%) were classified as secondary APS (sAPS) according to the published criteria. The mean age was 35 ± 11.5 vs. 36.6 ± 11.7 years, the mean disease duration was 98 ± 66 vs. 102 ± 76 months and the mean duration of follow-up was 82 ± 72 vs. 70 ± 64 months in the sAPS and non-sAPS groups respectively (p > 0.05). The mean number of ACR criteria fulfilled by the patients was similar (6 ± 1.4 vs. 6 ± 1.2) in both groups. Disease activity parameters (SLEDAI, patient and doctor visual analogue scales) were not significantly different between the groups at the time of the assessment. Total and weighted organ damage scores were significantly higher in the sAPS group (1.81 ± 1.21 vs. 0.94 ± 1.21, p = 0.004; 6.10 ± 4.46 vs. 2.76 ± 3.96, p = 0.001). The comparison of the individual items showed increased scores from ocular, neuropsychiatric and peripheral vascular damage. Conclusion: In this study we found that SLE patients with sAPS have higher organ damage scores than SLE patients without sAPS. Ocular, neuropsychiatric and peripheral vascular damage were found to be increased in patients with sAPS compared to the non-sAPS group. The presence of APS may significantly contribute to the organ damage in patients with SLE and specific measures are needed to avoid them.